2011
DOI: 10.20452/pamw.1033
|View full text |Cite
|
Sign up to set email alerts
|

Health care workers as second victims of medical errors

Abstract: IntroductIon "Second victims" are health care providers who are involved with patient adverse events and who subsequently have difficulty coping with their emotions. Growing attention is being paid to making system improvements to create safer health care and to the appropriate handling of patients and families harmed during the provision of medical care. In contrast, there has been little attention to helping health care workers cope with adverse events. objEctIvEs The aim of the study was to emphasize the im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
120
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(131 citation statements)
references
References 10 publications
8
120
0
3
Order By: Relevance
“…Second victims are identified as healthcare professionals who are traumatized by an unanticipated adverse event, medical error or patient-related injury (Scott et al, 2010). This concept was first introduced by Wu (2000) to describe the impact of mistakes on healthcare professionals and have been subsequently adopted in recent studies on the distress experienced by healthcare providers after an AE (Edrees et al 2011;Joesten et al 2015;Ullstr€ om et al 2014). Second victims in this review include healthcare professionals from nursing, medicine and allied health departments but exclude students.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second victims are identified as healthcare professionals who are traumatized by an unanticipated adverse event, medical error or patient-related injury (Scott et al, 2010). This concept was first introduced by Wu (2000) to describe the impact of mistakes on healthcare professionals and have been subsequently adopted in recent studies on the distress experienced by healthcare providers after an AE (Edrees et al 2011;Joesten et al 2015;Ullstr€ om et al 2014). Second victims in this review include healthcare professionals from nursing, medicine and allied health departments but exclude students.…”
Section: Introductionmentioning
confidence: 99%
“…Second victims in this review include healthcare professionals from nursing, medicine and allied health departments but exclude students. It was reported that nearly half of healthcare professionals have suffered the second victim phenomena throughout their careers (Edrees et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…no experience, observation or personal involvement) is associated with emotional distress and decreased professional quality of life. Although we know that healthcare providers desire coworker support and find it helpful when coping with an error or adverse event (Christensen et al, 1992;Edrees, Paine, Feroli, & Wu, 2011;Engel et al, 2006), this is the first study to examine whether coworker support moderated the impact of an error or adverse event on these outcomes. Overall, we found that a significant number of healthcare providers reported observing or being involved in an adverse patient event during the preceding 12 months.…”
mentioning
confidence: 97%
“…As many as half of all healthcare providers will experience "second victim" phenomena during their professional lives (Edrees, Paine, Feroli, & Wu, 2011). Yet, there is a paucity of studies that investigate the NP experience.…”
Section: Researchmentioning
confidence: 99%